ESTETIKA MISTIS DALAM PERSPEKTIF FILSAFAT SENI - Putu Maria Ratih Anggraini; Luh Putu Cita Ardiyani (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2023)
The material world and the spiritual world are two worlds side by side in human life. The material world can be recognized by the sensed experience of everyday life, while the spiritual world requires a separate intermediary to reach it because it is a world that is not sensed. The spiritual world can be understood by humans and also internalized through religious institutions, philosophical institutions and artistic institutions. This life is a colossal unity, between humans and society, between humans and nature, between humans and the magical spirit world, between humans and the entire cosmic system of this universe. Humans must align themselves with the cosmos if they want to live safely in this mortal world. Humans unite themselves with objects outside themselves and from there find their identity. The purpose of human life is to emphasize the inner aspect so that the outer aspect becomes in order in harmony with the essence. Humans can reach the abstract world through art, because in essence art is a feeling, namely an atmosphere, feeling, and an aesthetic experience in the form of emotions that are aroused by an artistic environment and situation. It is this universal feeling that leads to the highest peak of happiness which makes the aesthetic experience a religious experience.